Carbon Sequestration in Mineralogy: Potential of Ultramafic Rocks for CO₂ Storage - Sunidhi Rajput (International Journal of Minerals, 2025)
The increasing concentration of atmospheric carbon dioxide (CO₂) due to anthropogenic activities has necessitated the development of effective carbon sequestration strategies. Mineral carbonation, particularly utilizing ultramafic rocks, has emerged as a promising approach for long-term CO₂ storage. This review explores the potential of ultramafic rocks in sequestering CO₂, discussing their mineral composition, reaction mechanisms, advantages, and challenges associated with their utilization in carbon capture and storage (CCS). Additionally, advancements in enhancing mineral carbonation efficiency, including pre-treatment techniques and microbial-assisted sequestration, are examined. The use of ultramafic rocks offers a natural and permanent solution for CO₂ mitigation, with significant implications for climate change mitigation. The ability of these rocks to form stable carbonate minerals upon reacting with CO₂ makes them a reliable option for reducing greenhouse gas emissions. However, improving reaction rates and addressing energy and economic constraints remain key research areas. Furthermore, understanding the geological distribution of ultramafic rocks and integrating their use with industrial processes can enhance their practical applicability. In order to speed up carbonation, it is crucial to optimize reaction conditions and investigate novel catalysts, as demonstrated by recent developments in laboratory and field tests. The incorporation of microbial and enzymatic processes further presents a novel avenue for enhancing CO₂ sequestration efficiency. This review emphasizes the need for interdisciplinary research to bridge gaps between geology, chemistry, and engineering to maximize the effectiveness of mineral carbonation. Future efforts should focus on pilot-scale projects, life cycle assessments, and policy frameworks to ensure the sustainable implementation of this technology. Overall, ultramafic rock-based carbon sequestration presents a viable and durable strategy for combating global carbon emissions while contributing to the advancement of CCS technologies.
Keywords: Mineral carbonation; carbon dioxide sequestration; carbon mineralization; climate change mitigation; geological CO₂ storage; ultramafic rocks